Development of a 0.15 μm GaAs pHEMT Process Design Kit for Low-Noise Applications - Igor M. Dobush (MDPI AG, 2021)
This work presents a process design kit (PDK) for a 0.15 μm GaAs pHEMT process for low-noise MMIC applications developed for AWR Microwave Office (MWO). A complete set of basic elements is proposed, such as TaN thin film resistors and mesa-resistors, capacitors, inductors, and transistors. The developed PDK can be used in technology transfer or education.